A View of Underground Coal Mining in the 21st Century (The Australasian Institute of Mining and Metallurgy, 1988)
The intent of this address is to look forward into the 21st Century and present certain thoughts as to how underground coal mining might be conducted. The views in this talk are based principally on the author's experience with mining practices in the United States. It may be difficult to accept, but the 21st Century is a mere 12 years away. What new techniques will be available? To develop an understanding of the way in which technology has been and could be changing, a two- stage analysis is made of mining technology for U.S. Coal. The first phase covers the period 1975 to the present, while the second includes 1960 to 1975. This historical perspective includes a view of underground production by mining methods, considerations of labour productivity, and a review of accident and fatality rates. Several topics are important features of this historical analysis. Among the most significant are: (1) the introduction of Ion-wall mining technology into U.S. underground coal mines, (2) the use of computers to assist in mine planning and design activities, (3) major efforts to improve health and safety performance, with emphasis on underground dust control, and (4) improvements in mining equipment with an eye towards increased reliability and up-time performance. Based on that historical perspective, projections are made in three increments. The first being immediately at the turn of the century, the second being a dozen or so years beyond that, and the third being at the quarter point of the 21st Century.